Perception of Nurses on Needs of Family Members of Patient Admitted to Critical Care Units of Teaching Hospital, Chitwan Nepal: A Cross-Sectional Institutional Based Study - Ishwori Khatri Chhetri; Bedantakala Thulung (Nursing Research and Practice)
Background. Critical care units’ nurses should seek to develop collaborative relationships with patients’ family members based on their needs and help them to cope with their distress. The objective of this study was to find out the perception of nurses on needs of family members of patients admitted to critical care units. Methods. A descriptive cross-sectional study was conducted in Chitwan Medical College Teaching Hospital among all 65 nurses working in critical care units. Ethical clearance was obtained from Chitwan Medical College Institutional Review Committee. Data were collected from March 27 to April 25, 2016, using Critical Care Family Needs Inventory (CCFNI). Obtained data were analyzed using descriptive and inferential statistics. Results. This study found that mean age of the nurses was 23.98 ± 4.05 years. More than half of the nurses had completed PCL in nursing (52.3%) and had 1-5 years of experience in critical care units (58.5%). Nurses ranked the needs for assurance as most important needs with mean percent (86.25%) followed by needs for information (78.58%), need for comfort (69.59%), needs for closeness (69%), and needs for support (64.13%). Out of 45 family needs, 81.5% of nurses perceived that knowing about patient treatment is very important for family members. Married nurses perceived the needs for support to be more important than unmarried nurses (p=0.04) whereas unmarried nurses perceived the needs for information to be more important than married (p=<0.01). There was significant difference on perception of nurses on needs of assurance with ethnicity (p=0.009) and critical care experience (p=0.04).